Response Surface Methodology used in the Optimization of RP-HPLC Condition for Quantitative Analysis of Carmine and Rhodamine B - Reyna Nuvitasari; Abdul Rohman; Sudibyo Martono (Indonesian Journal of Pharmacy, 2019)
The objective of this study was to optimize reversed-phase high-performance liquid chromatography (RP-HPLC) using an experimental design approach based on the response surface methodology of Central Composite Design (CCD) for separation and analysis of carmine (CAR) and Rhodamine B (RHO) in lipstick products. Some factors (independent variables) responsible for RP-HPLC separation including pH of buffer phosphate (X1), the acetonitrile ratio (X2), flow rate of mobile phase (X3), and column temperature (X4) were investigated. While, the responses (dependent variables) evaluated were resolution between CAR and RHO (Y1), tailing factor of CAR (Y2), tailing factor of RHO (Y3), retention time of CAR (Y4), retention time of RHO (Y5), peak area of CAR (Y6) and peak area of RHO (Y7). CCD showed that separation of CAR and RHO was influenced by these independent variables (factors). The optimum predicted conditions for the separation of CAR and RHO based on statistical results was pH buffer of 3.4, ACN 55%, the flow rate of 1.1 mL/min and column temperature of 35oC with the desirability of 1. Both CAR and RHO were clearly separated using optimum conditions, as suggested by CCD. The developed techniques were effective for optimizing chromatographic separation, therefore, the time consumption and a large number of running could be hindered.